The obese patient undergoing nonbariatric surgery. Issue 3 (June 2016) - Bluth, Thomas; Pelosi, Paolo; de Abreu, Marcelo Gama
Abstract : Purpose of review: This article provides the reader with recent findings on the pathophysiology of comorbidities in the obese, as well as evidence-based treatment options to deal with perioperative respiratory challenges. Recent findings: Our understanding of obesity-associated asthma, obstructive sleep apnea, and obesity hypoventilation syndrome is still expanding. Routine screening for obstructive sleep apnea using the STOP-Bang score might identify high-risk patients that benefit from perioperative continuous positive airway pressure and close postoperative monitoring. Measures to most effectively support respiratory function during induction of and emergence from anesthesia include optimal patient positioning and use of noninvasive positive pressure ventilation. Appropriate mechanical ventilation settings are under investigation, so that only the use of protective low tidal volumes could be currently recommended. A multimodal approach consisting of adjuvants, as well as regional anesthesia/analgesia techniques reduces the need for systemic opioids and related respiratory complications. Summary: Anesthesia of obese patients for nonbariatric surgical procedures requires knowledge of typical comorbidities and their respective treatment options. Apart from cardiovascular diseases associated with the metabolic syndrome, awareness of any pulmonary dysfunction is of paramount. A multimodal analgesia approach may be useful to reduce postoperative pulmonary complications.